Prevalence and trend of atrial fibrillation and its associated risk factors among the population from nationwide health check-up centers in China, 2012–2017 - Tao Sun; Tao Sun; Mao Ye; Mao Ye; Fang Lei; Fang Lei; Juan-Juan Qin; Juan-Juan Qin; Ye-Mao Liu; Ye-Mao Liu; Ze Chen; Ze Chen; et al. (Frontiers in Cardiovascular Medicine, 2023)
BackgroundAtrial fibrillation (AF) is the most prevalent cardiac arrhythmia, which poses huge disease burdens in China. A study was conducted to systematically analyze the recent prevalence trend of AF and age-related disparities in AF risk among the nationwide healthy check-up population.MethodWe conducted a nationwide cross-sectional study involving 3,049,178 individuals ≥35 years from health check-up centers to explore the prevalence and trend of AF by age, sex, and region from 2012 to 2017. Additionally, we analyzed risk factors associated with AF among the overall population and different age groups via the Boruta algorithm, the LASSO regression, and the Logistic regression.ResultThe age-, sex-. and regional-standardized prevalence of AF kept stable between 0.4%–0.45% among national physical examination individuals from 2012 to 2017. However, the prevalence of AF showed an undesirable upward trend in the 35–44-year age group (annual percentage changes (APC): 15.16 [95%CI: 6.42,24.62]). With increasing age, the risk of AF associated with the overweight or obesity gradually exceeds that associated with diabetes and hypertension. In addition to traditional leading risk factors such as age≥65 and coronary heart disease, elevated uric acid and impaired renal function were tightly correlated with AF in the population.ConclusionThe significant rise in the prevalence of AF in the 35–44 age group reminds us that in addition to the elderly (the high-risk group), younger people seem to be in more urgent need of attention. Age-related disparities in AF risk also exist. This updated information may provide references for the national prevention and control of AF.